Consumismo, educación y derecho - Valdez Torres, Liliana Guadalupe (Universidad Michoacana de San Nicolás de Hidalgo, 2021)
The society of the 21st century is characterized by important transformations in science, technology, economy and society, which has generated a particular way of life and various problems, among which is consumerism, in which changes in production have been determinant and have led to a dehumanized and individualistic consumption. Likewise, consumerism has had a negative impact on the environment, people's health and behavior, and has also led to harmful socio-cultural changes; This, in the case of Mexico, requires the implementation of actions to eliminate or significantly reduce the problem of consumerism, for which it is necessary to structure solid foundation through education, law, government, and public and private institutions that help to create and apply strategies that lead the population to healthier and more responsible behaviors, That is to say, to achieve responsible consumption and social responsibility, which implies having a nade quate regulatory framework, streng the in the educational system as well as public institutions directly related to the problem, as is the case of the Federal Consumer Protection Agency, always aspiring to achieve better living conditions for Mexicans, for the common good.

La sociedad del siglo XXI se caracteriza por importantes transformaciones en la ciencia, la tecnología, la economía y la sociedad, lo cual ha generado una particular forma de vida y diversos problemas, entre los que se encuentra el consumismo, en el que han sido determinantes los cambios en la producción y ha propiciado un consumo deshumanizado e individualista. Asimismo, el consumismo ha impactado negativamente al medio ambiente, la salud de las personas y las conductas de éstas, traduciéndose también en nocivos cambios socioculturales; lo anterior, en el caso de México, obliga a la implementación de acciones que eliminen o disminuyan significativamente el problema del consumismo, para lo cual es necesario estructurar bases sólidas mediante la educación, Derecho, gobierno e instituciones públicas y privadas que coadyuven a crear y aplicar estrategias que conduzcan a la población a conductas más sanas y responsables, es decir, a lograr el consumo responsable y la responsabilidad social, lo cual implica contar con un adecuado marco normativo, fortalecer el sistema educativo así como instituciones públicas relacionadas directamente con la problemática, como es el caso de la Procuraduría Federal del Consumidor, aspirando siempre a lograr mejores condiciones de vida de los mexicanos, al bien común.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2021-0168; Humanidades; Consumo; Producción; Educación; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3652